(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
Constitutional reforms represent a fundamental transformation of the legal order of any state. In Uzbekistan, the 2023 constitutional amendments introduced comprehensive changes that directly affected the entire system of normative legal acts. This article examines the scope, mechanisms, and legal consequences of constitutional changes on the hierarchy of normative legal acts, analyzing the alignment processes, legislative revisions, and emerging challenges in law-enforcement practice. The study employs doctrinal analysis, comparative legal method, and systemic interpretation to establish the degree of normative conformity achieved following constitutional reform. The findings indicate that while substantial progress has been made in harmonizing national legislation, certain gaps and inconsistencies persist that require further systematic legislative attention.